2016
DOI: 10.5334/ohd.25
|View full text |Cite
|
Sign up to set email alerts
|

Data from ‘Graphic Medicine’ as a Mental Health Information Resource: Insights from Comics Producers

Abstract: This dataset contains the full text transcripts from 15 semi-structured interviews (approximately 44,100 words) conducted during November and December 2014 with participants involved in various aspects of the process of health-related comics production. These participants are authors and publishers and their work is publicly recognised in the comics community. The dataset has been deposited in the Open Health Data Dataverse repository as a zipped folder containing 15 individual simple text files corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…These results contradict previous research findings that attest the ability of comics to improve the involvement with health information [82] through character identification [51] and "narratives of lived experiences" [61]. More positive evaluations of the influencer post suggest that pictures that tell stories (and feature influencers) allow the affected individuals to deal better with their experiences and increase the acceptance of mental health issues [63]. Preference of format further suggests that individuals seek content that boosts their esteem or content with a "human touch"-results that are also in line with previous research findings: Pettigrew and colleagues [35] found that a spokesperson who possessed considerable knowledge on the topic was considered as an ideal candidate to speak up about health issues.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…These results contradict previous research findings that attest the ability of comics to improve the involvement with health information [82] through character identification [51] and "narratives of lived experiences" [61]. More positive evaluations of the influencer post suggest that pictures that tell stories (and feature influencers) allow the affected individuals to deal better with their experiences and increase the acceptance of mental health issues [63]. Preference of format further suggests that individuals seek content that boosts their esteem or content with a "human touch"-results that are also in line with previous research findings: Pettigrew and colleagues [35] found that a spokesperson who possessed considerable knowledge on the topic was considered as an ideal candidate to speak up about health issues.…”
Section: Discussioncontrasting
confidence: 90%
“…The potentials of comics have already been discussed in a variety of studies, some of which have also been conducted in the health communication context. Although their potential to induce behavioral changes is often neglected [57,60], comics' "psychologi-cal and cognitive effects of embodiment and narrative (can translate) lived experiences into narratives" [61] (p. 35), an aspect that has been found to benefit both anti-stigma communication and mental health communication [56,62,63].…”
Section: Comicmentioning
confidence: 99%
“…This article, which is part of a wider study examining 'graphic medicine', presents the results of a study exploring the attitudes around comics and their use amongst staff and students at a mental health NHS Trust that has yet to utilise comics in its training programmes. A previously published article and dataset provided observations from interviews with comics creators and distributors (Farthing and Priego, 2016a;2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The common characteristic across all the diverse applications of comics [2], [3], [4], [5], [6], [7], [8], [9], [10] is that with a smart mixture of text or/and other visual information, artists communicate the content by drawing the viewer attention to specific areas.…”
Section: Introductionmentioning
confidence: 99%